Experimental and theoretical studies of the Xe-OH(A/X) quenching system - Kłos, J; McCrudden, G; Brouard, M; Perkins, T; Seamons, SA; Herráez-Aguilar, D; Aoiz, FJ (American Institute of Physics, 2018)
New multi-reference, global ab initio potential energy surfaces (PESs) are reported for the interaction of Xe atoms with OH radicals in their ground X2Π and excited A2Σ+ states, together with the non-adiabatic couplings between them. The 2A' excited potential features a very deep well at the collinear Xe-OH configuration whose minimum corresponds to the avoided crossing with the 1A' PES. It is therefore expected that, as with collisions of Kr + OH(A), electronic quenching will play a major role in the dynamics, competing favorably with rotational energy transfer within the 2A' state. The surfaces and couplings are used in full three-state surface-hopping trajectory calculations, including roto-electronic couplings, to calculate integral cross sections for electronic quenching and collisional removal. Experimental cross sections, measured using Zeeman quantum beat spectroscopy, are also presented here for comparison with these calculations. Unlike similar previous work on the collisions of OH(A) with Kr, the surface-hopping calculations are only able to account qualitatively for the experimentally observed electronic quenching cross sections, with those calculated being around a factor of two smaller than the experimental ones. However, the predicted total depopulation of the initial rovibrational state of OH(A) (quenching plus rotational energy transfer) agrees well with the experimental results. Possible reasons for the discrepancies are discussed in detail.